Ambiguïtés de la réception critique de l’exposition « Canadian Women Artists », Riverside Museum, New York, 1947 - Pageot, Édith-Anne (RACAR : Revue d'art canadienne / Canadian Art Review, 2000)
In the spring of 1947, the Riverside Museum in New York presented the travelling exhibition, “Canadian Women Artists,” bringing together paintings by seventy-two Canadian women, including Emily Carr, Kathleen Daly, Prudence Heward, Anne Savage, Marian D. Scott, Jori Smith and Edna Taçon. The Canadian organizers aimed to make women more visible and to include them within the dominant artistic directions in Canada. The mobilization of women into an international exhibition was without historical precedent. In this respect, the event took on a fundamental importance for the inscription of women in the history of Canadian art. Nevertheless, a heterogeneous collection of works was favoured, and this article intends to show that this orientation weakened the content of the exhibition, favouring questions extraneous to the specificity of the works and to the diffusion of women’s art. Only Anne Francis, of the Ottawa Citizen, used the exhibition as an opportunity to denounce the masculine exclusivity of the notion of the creator. Elizabeth Wyn Wood, to whom the introduction of the catalogue had been entrusted, availed herself of the opportunity to valorize the idea of a Canadian artistic temperament which took account of the cultural diversity of the country. The American critic, E.A. Jewell, saw in the exhibition the manifestation of a nationalism that he tried to define by reference to the Group of Seven. For Nettie S. Horch, the director of the Riverside Museum, “Canadian Women Artists” shouldered political aims that overshadowed a singular emphasis on the contribution of women. According to her, the event took up, once more, the efforts of collaboration between nations undertaken by the United States before the war. The feminist purpose, potentially disturbing, was thus reduced by political and ideological considerations.